KEPASTIAN HUKUM TERHADAP PERSEROAN TERBATAS PASCA BERAKHIRNYA KEPAILITAN - Calvin Ulri Rompas Sumual; Yuhelson Yuhelson; Cicilia Julyani Tondy (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to review and analyze the legal certainty of Limited Liability Companies (PT) after the end of bankruptcy, a condition in which the company is declared unable to fulfill its obligations to creditors in accordance with Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations. Bankruptcy often brings complex legal consequences, both for the entity concerned and the creditors. In this context, legal certainty plays an important role to ensure that the legal rights of all parties involved are protected and respected. This research uses a normative juridical approach to evaluate how existing laws provide legal certainty for Limited Liability Companies after the end of bankruptcy. The findings in this study show that although there are fairly clear rules regarding the bankruptcy process, there are deficiencies in the regulations related to the restoration of the legal and operational status of Limited Liability Companies after bankruptcy is declared over. These deficiencies can lead to legal uncertainty, which has the potential to hamper the recovery and continuity of the Limited Liability Company's business, as well as pose a risk of further legal disputes. The results of this study indicate the need to strengthen the legal framework to ensure that after bankruptcy, Limited Liability Companies can resume operations with clear legal certainty. More detailed regulations and appropriate implementation guidelines are needed to ensure that Limited Liability Companies, as legal entities, have a solid foundation to continue their business activities without facing ongoing legal uncertainty. Thus, legal certainty becomes a key element in supporting post-bankruptcy business stability and sustainability